Individual Targeting Increases Control Over Inter-Individual Variability in Simulated Transcranial Electric Fields - Jan-Ole Radecke; Asad Khan; Andreas K. Engel; Carsten H. Wolters; Till R. Schneider (IEEE Access, 2020)
Transcranial electric stimulation (tES) induces electric fields that propagate in the brain and depend on individual anatomies. The interaction between the electric fields and individual anatomies may contribute to the heterogenous results that are commonly observed across tES studies in humans. Targeted tES is able to account for some of these individual factors by adapting the electric field to the stimulation target. Here, the effect of individually targeted tES on simulated intracranial electric fields was evaluated in head models of twenty-one participants using the finite-element method (FEM). For all participants, two individually targeted tES montages were compared to a fixed stimulation montage that was not individually optimized. For a simulated parietal stimulation target with three different orientations, individual current densities showed varying intensities near the lower limit at which physiological efficacy of electric fields can be assumed. However, targeting algorithms were able to control different electric field properties, by either maximizing the target current densities or by increasing the specificity of electric fields with respect to target location and orientation. Electric fields were constrained by individual anatomical properties, but still showed considerable variation for the given parietal stimulation target across participants. Thus, we present findings of inter-individual variability within the same cortical region to complement recent studies that showed large variation across cortical regions in a single FEM head model. Our results support the usage of individual targeting for enhancing the efficacy of tES and for elucidating the underlying mechanisms of tES. At the same time, residual variability in electric fields is suggested to be utilized for the explanation of individual differences in the tES outcome.